2021
DOI: 10.3390/molecules26020301
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Physical, Chemical and Microbiological Stability of Losartan Potassium 5 mg/mL Extemporaneous Oral Liquid Suspension

Abstract: Extemporaneous oral liquid preparations are commonly used when there is no commercially available dosage form for adjustable dosing. In most cases, there is a lack of stability data to allow for an accurately assigned shelf life and storage conditions to give greater confidence of product safety and efficacy over its shelf life. The aim of this study was to evaluate the physical, chemical and microbiological stability of an extemporaneous oral liquid suspension of losartan potassium, 5 mg/mL, used to treat pae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…No similar studies were found with test results for storage at oven temperature of 40°C. However, a study carried out in Ireland showed that an extemporaneous suspension of losartan potassium (5 mg/mL) remained stable in the refrigerator and at room temperature for 28 days 13. The same period was determined by Alfagih et al 14.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…No similar studies were found with test results for storage at oven temperature of 40°C. However, a study carried out in Ireland showed that an extemporaneous suspension of losartan potassium (5 mg/mL) remained stable in the refrigerator and at room temperature for 28 days 13. The same period was determined by Alfagih et al 14.…”
Section: Discussionmentioning
confidence: 79%
“…Few studies related to liquid formulation of losartan potassium have been published,13 14 so the purpose of this study is to develop a liquid formulation containing losartan potassium using the raw material and a simple manufacturing process suitable for reproduction in a University Hospital in Brazil. A high-performance liquid chromatography (HPLC) method was validated in order to carry out stability tests of the developed formulation.…”
Section: Introductionmentioning
confidence: 99%
“…Losartan has an 8 mg/mL water solubility level with a pKa of 5.5. A 5 mg/mL formulation has recently been studied [ 102 ], and directions for the preparation of a 2.5 mg/mL suspension are contained in the package insert [ 103 ].…”
Section: The Next Wave Of Oral Liquid Formulation Development—formula...mentioning
confidence: 99%
“…Therefore, extemporaneous compounding of losartan oral suspension is performed in various hospitals globally [8].…”
Section: Introductionmentioning
confidence: 99%